Nitrogenase promoter-lacZ fusion studies of essential nitrogen fixation genes in Bradyrhizobium japonicum I110. - Yun, A C (1986)
DNA fragments containing either the nifD or nifH promoter and 5' structural gene sequences from Bradyrhizobium japonicum I110 were fused in frame to the lacZ gene. Stable integration of these nif promoter-lacZ fusions by homologous double reciprocal crossover into a symbiotically nonessential region of the B. japonicum chromosome provided an easy assay for the effects of potential nif regulatory mutants. The level of beta-galactosidase activity expressed from these two nif promoter-lacZ fusions was assayed in bacteroids of B. japonicum I110 wild type and Fix mutants generated by transposon Tn5 mutagenesis and identified in the accompanying paper. No nif-positive regulatory mutants were identified from among an array of Fix- mutants in which Tn5 was inserted 9 kilobase pairs upstream of the nifDK operon and within the 18-kilobase-pair region separating the nifDK and nifH operons. This result indicates that there are no genes in these regions involved in the regulation of nitrogenase structural gene expression. Interestingly, the level of beta-galactosidase activity expressed from the nifH promoter was twice that expressed from the nifD promoter, suggesting that the normal cellular level of the nifH gene product in bacteroids is in a 2:1 ratio with the nifD gene product instead of in the 1:1 stoichiometry of the nitrogenase enzyme complex.